Kualitas demokrasi di Indonesia dalam era digital: Peran teknologi dalam meningkatkan atau melemahkan demokrasi - Gina, Lia (Maliki Interdisciplinary Journal, 2026)
The advancement of digital technology has had a significant impact on the quality of democracy in Indonesia. This study aims to examine the role of digital technology in both strengthening and potentially weakening democracy. The research applies a qualitative descriptive approach through a literature review, utilizing secondary data from academic journals, books, and previous studies. The findings reveal that digital technology can enhance political participation, expand access to information, and promote transparency and government accountability. However, it also poses several challenges, including the spread of hoaxes, misinformation, social polarization, and the potential manipulation of public opinion. Therefore, improving digital literacy, strengthening regulations, and fostering collaboration between the government and society are essential to establish a healthy digital environment. In conclusion, digital technology can be effectively utilized to support a more inclusive, critical, and sustainable democracy in Indonesia.